A Review of the Clinical Evidence for Complementary and Alternative Medicine in Huntington's Disease. (26th August 2019) - Yu, Margaret; Bega, Danny
Background: There is a lack of published guidelines related to the use of complementary and alternative medicine (CAM) for Huntington's disease (HD). We conducted a review of the literature to summarize the available evidence for various mind–body practices and nutraceuticals. Methods: PubMed and Cochrane Library electronic databases were searched independently from inception to February 2019 by two independent raters. Studies were classified for the level of evidence (Class I, II, III, or IV) according to the American Academy of Neurology (AAN) classification scale. Results: Randomized controlled trials in HD were reviewed for mind–body interventions (dance therapy, music therapy, and exercise), alternative systems (traditional Chinese medicine [TCM]), and nutraceuticals/diet (aminooxyacetic acid [AOAA], coenzyme q10, creatine, cannabinoids, alpha-tocopherol, eicosapentaenoic acid, idebenone, levocarnitine, and triheptanoin). Few studies met AAN Class I or II level of evidence for benefits, and these are highlighted. Discussion: There is a relative paucity of clinical trials examining CAM modalities in HD when compared to other neurodegenerative disorders. Currently, there is no evidence supporting disease modification or symptom improvement with any specific dietary or nutraceutical supplement for HD. Supervised exercise and contemporary dance are safe for people with HD, but more robust studies are warranted to guide specific recommendations for these and other mind–body interventions.